2011
DOI: 10.1108/14684521111176516
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge sharing in wiki communities: an empirical study

Abstract: Purpose -Prior research indicates that the success of a virtual community relies on its ability to allow community members to share knowledge interactively. Wiki applications are web-based hypertext applications that facilitate collaborative authoring, and have been widely adopted by virtual communities to facilitate knowledge sharing and accumulation. Nevertheless very few studies have empirically investigated the dynamics of how these applications contribute to the development and continuity of virtual commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…For example, a number of studies indicated trust as a positive factor that motivates knowledge sharing intention [20], which results in the contribution to the actual knowledge sharing behavior. However, there are some other studies suggesting that the influence of trust in knowledge sharing behavior is not significant [14].…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…For example, a number of studies indicated trust as a positive factor that motivates knowledge sharing intention [20], which results in the contribution to the actual knowledge sharing behavior. However, there are some other studies suggesting that the influence of trust in knowledge sharing behavior is not significant [14].…”
Section: Introductionmentioning
confidence: 93%
“…However, other studies [9], [14] rejected the assumption of motivational impact of trust. Specifically, the type of trust examined in the two studies [9], [14] was integrity-based trust which refers to the belief that people in the community would refrain from taking advantage of each other (opportunistic behavior). One possible explanation is that the two communities being examined were based on less risky knowledge sharing relationships such as among individuals who hardly interact or have close working relationships.…”
Section: Findings Discrepancies and Explanationmentioning
confidence: 99%
See 2 more Smart Citations
“…Wiki is web pages or a website that people can directly edit, update, modify or delete (Wang and Wei 2011;Laughton 2011;Menkhoff et al 2011;Frumkin 2005). Wiki can be linked to a collaborative word processing document allowing multiple users from different locations to collaborate in real-time (Liu et al 2010;Frumkin 2005).…”
Section: Web 20 and Wiki Characteristicsmentioning
confidence: 99%